The determinants of capital structure: Empirical evidence from Chinese real estate and construction listed firms in 2016 - ZHANG, Yuanjing (2017)
Abstract Purpose – The purpose of this paper is to investigate the determinants of the capital structures of the Chinese listed real estate and construction firms. Design/methodology – The paper chooses the cross-sectional data from Chinese listed property and construction companies in 2016 to carry out the multiple regression. Findings – The findings confirm that the firms’ total debt ratio is significantly and positively related to the profitability (ROA), firm size (Age and LnAt), and NDTS, while the long-term debt ratio of the listed firms in property and construction sectors statistically increases with the firm size (Age and LnAt) and decreases with profitability (ROA). Both leverage ratios are measured by the book value. Besides, the result shows an insignificant positive relationship between firm tangibility and two leverage ratios and a negative correlation between firm NDTS and the long-term debt ratio. As for the factor of growth opportunities, there is no significantly related to the total debt ratio and the long-term debt ratio. Further, there is no statistical difference in capital structure in real estate and construction firms. Research limitation –The limitation of this paper is the scale of sample selection and the empirical method employed. Value – This paper selects the latest and sufficient cross-sectional data from real estate and construction industries to provide the empirical evidence on the capital structure determinants.